Electrocatalytic benchmarking of ruthenium-based bimetallic anodes for the electrocatalytic oxidation of biomass-derived wastewater - Lyndi E. Strange; Bhanupriya Boruah; Nickolas W. Riedel; Mark E. Bowden; Mark H. Engelhard; Juan A. Lopez-Ruiz (Applied Catalysis O: Open)
In this paper, we report on the synthesis, characterization, and use of ruthenium oxide (RuO2) doped with a secondary metal (M2) (i.e., RuM2) to enhance electrocatalytic activity and stability for the electrocatalytic oxidation (ECO) of biomass-derived wastewaters. We used different electrochemical methods such as cyclic voltammetry (CV), electrochemical active surface area (ECSA), and activity analysis (analogous to the Tafel analysis) as well as physical characterization such as grazing incidence X-ray diffraction, X-ray photoelectron spectroscopy, and scanning electron microscopy to understand how the addition of M2 affects electrocatalytic performance. Since the electrode surface can restructure once the RuM2 anodes are exposed to reaction conditions, the physical properties of the fresh RuM2s might not accurately represent the anode surface under reaction conditions. Therefore, we characterized the RuM2 using our proposed in situ electrocatalytic benchmarking protocol. We observed an increase in ECSA, which may be attributed to enhanced charge transfer for the pH ranges evaluated. Furthermore, the presence of organic (and inorganic) compounds in wastewater generated during the hydrothermal liquefaction (HTL-WW) of food waste impacted the ECO performance in varied ways, depending on M2, the electrolyte composition, and anodic half-cell potential, thereby highlighting the importance of characterizing the RuM2s under realistic reaction regimes. The in situ electrocatalytic benchmarking protocol can quickly assess if the presence of M2 improves the ECO performance, thus saving time and resources compared to excessive ex situ physical characterization, testing, and product analysis. This foundational work provides the basis for characterization and benchmarking of electrodes for the ECO of organic compounds.